Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1371/journal.pone.0237733
|View full text |Cite
|
Sign up to set email alerts
|

Vibration threshold in non-diabetic subjects

Abstract: Measuring vibration perception threshold (VPT) accurately classifies and quantifies the severity of loss of vibration perception. A biothesiometer (Bio-thesiometer ® ; Bio Medical Instrument Co, Ohio, USA) appears to be the most suitable tool to determine VPT due to its low inter-rater variability and low occurence of adaption to the sensation. Different VPT values for a biothesiometer have been described, however, specification on age, height and different measurement locations is currently lacking. The objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
3
1
Order By: Relevance
“…This study also showed a similar result. Previous studies have reported the correlation between height and VPT in non-diabetic subjects ( 20 ) and patients with diabetes ( 11 ) and no similar correlation was found in our gout population. A significant association was also found between ESR (inflammatory markers of disease activity) and abnormal VPT in this study.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…This study also showed a similar result. Previous studies have reported the correlation between height and VPT in non-diabetic subjects ( 20 ) and patients with diabetes ( 11 ) and no similar correlation was found in our gout population. A significant association was also found between ESR (inflammatory markers of disease activity) and abnormal VPT in this study.…”
Section: Discussioncontrasting
confidence: 76%
“…However, up to now, no study specifically investigated associated factors with VPT in patients with gout. A variety of factors are related to VPT and the correlation between age and VPT has been widely reported, both in the general population ( 20 ) and in patients with diabetes ( 11 ). Similarly, this study also confirmed the independent correlation between abnormal VPT and age in patients with gout.…”
Section: Discussionmentioning
confidence: 99%
“…While the possible causes of these changes are manifold, including repeated trauma, focal nerve entrapment, and ischemia, the normal process of biological aging is thought to be an important contributing factor. The most suggestive evidence of central-peripheral distal axonopathy is the progressive increase in vibratory threshold with age, more in the lower limb (great toe) than in the upper limb (finger) [ 154 , 155 , 156 , 157 , 158 , 159 , 160 ]. Vibration perception also decreases with body height, which is consistent with a length-dependent axonopathy [ 160 ].…”
Section: Relationship To Neuropathies Of Endogenous Originmentioning
confidence: 99%
“…It can be used as a tool for research into occupational health to screen workers at workplace for peripheral neuropathy caused by direct vibration or toxic substances [7,8]. The VPT is an effective predictor of the risk of trophic ulceration of the feet and risk of amputation in diabetic patients and, therefore can be used to target foot-care education as a preventive measure [9][10][11][12][13]. The VPT is also widely applied in community-based research, occupational health screening in industries and ambulatory clinics [5].…”
Section: Introductionmentioning
confidence: 99%